(untitled) (Research, Society and Development, 2024)
Thrombocytopenia is defined as a platelet count of less than 150,000/mm3, through blood collected with EDTA, and its occurrence is around 18% to 35% of newborns in the Neonatal ICU, with 80% occurring in the first week of life, commonly in extremely premature newborns, weighing <1000g. The World Health Organization (WHO) defines thrombocytosis as a platelet count above 600,000/mm3. Other institutions define this pathology as platelets from 400,000, 6000,000, and 900,000/mm3. Thrombopoietin is widely considered the most effective stimulator of platelet production, acting on the proliferation of megakaryotic progenitors. The objective of this research is to present a case study, analyzing a full-term newborn, born by vaginal birth, who underwent infectious screening due to maternal factors when thrombocytopenia was identified. Therefore, the study seeks to evaluate the evolution of this patient concerning autoimmune neonatal thrombocytopenia and its main complications.